Implementation of Hybrid Learning and PAI Teachers' Communication Methods in Improving Students' Motivation and Learning Achievement - Kholik; Fajar Syarif (Educazione: Journal of Education and Learning, 2025)
This study aims to analyze the implementation of hybrid learning and the communication strategies employed by Islamic Religious Education (PAI) teachers to enhance student motivation and learning achievement. Utilizing a qualitative descriptive approach with a case study design, this research was conducted at SMP Patriot Kota Bekasi. Data were collected through participatory observation, in-depth interviews, and documentation involving 37 informants, including school administrators, the PAI teacher, students, and parents. The findings reveal that implementing hybrid learning, specifically through Flipped Classroom and Blended Learning models, effectively mitigates student boredom and restores enthusiasm compared to prolonged full online instruction. Furthermore, the PAI teacher’s strategic communication—such as establishing a dedicated WhatsApp group for pre-class motivation, providing personalized attention, offering consistent appreciation, and fostering an interactive learning atmosphere—serves as a critical catalyst in rebuilding students' intrinsic drive. Consequently, these combined strategies significantly contribute to the improvement of students' character, motivation, and overall academic achievement in PAI subjects during the post-pandemic educational transition.